PtCSA / Cu2O / NF composite material and application of PtCSA / Cu2O / NF composite material in electrocatalytic reduction of nitrate into ammonia

By loading platinum on the Cu2O/NF electrode sheet, the PtCSA/Cu2O/NF composite material was constructed, and the problem of high cost of precious metal catalysts was solved, efficient removal of nitrates in water and ammonia was achieved, which significantly reduced the cost of catalyst use.

CN120138716AActive Publication Date: 2025-06-13ZHEJIANG UNIV OF TECH +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510324318.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-19
Publication Date
2025-06-13
Estimated Expiration
2045-03-19

AI Technical Summary

Technical Problem

In the prior art, precious metal catalysts such as palladium and platinum are expensive, which limit their promotion in large-scale applications, making it difficult to effectively remove nitrate contaminants in water.

Method used

Using PtCSA/Cu2O/NF composite material, platinum is loaded on Cu2O/NF electrode sheet by electrochemical deposition method to construct a single-atom-nano cluster gradient distribution structure to achieve ultra-low loading and efficient catalysis of precious metal platinum.

Benefits of technology

At low potential (-0.39V vs. RHE), the nitrate in water is efficiently converted into ammonia, removing nitrate contaminants in water, significantly reducing the cost of precious metal catalysts and improving atomic utilization.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120138716A_ABST
    Figure CN120138716A_ABST
Patent Text Reader

Abstract

The invention discloses a PtCSA / Cu2O / NF composite material and application thereof in electrocatalytic reduction of nitrate into ammonia, a preparation method of the PtCSA / Cu2O / NF composite material comprises the following steps: depositing Cu (OH) 2 on foamed nickel NF to obtain a Cu (OH) 2 / NF electrode plate, performing high-temperature calcination in a nitrogen atmosphere, taking the obtained CuO / NF electrode plate as a cathode, adopting an electrolyte solution as an electrolyte solution, and performing high-temperature calcination in a nitrogen atmosphere to obtain the PtCSA / Cu2O / NF composite material. The preparation method comprises the following steps: taking CuO as a cathode, carrying out electroreduction on an electrode by adopting an anode counter under a preset constant voltage to convert CuO on the cathode into Cu2O to obtain a Cu2O / NF electrode plate, and finally carrying out electrodeposition on the electrode plate to load Pt, thereby completing the preparation. According to the method, the atomic-scale dispersity of platinum is accurately regulated and controlled through an in-situ electrochemical deposition method, a monatomic-nanocluster gradient distribution structure (PtCSA / Cu2O / NF) is constructed, the ultra-low loading capacity of precious metal platinum is achieved, and the good application effect is achieved in the aspect of electrocatalytic reduction of nitrate into ammonia.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a Pt CSA / Cu 2 O / NF composite material and its application in electrocatalytic reduction of nitrate to ammonia. Background Art

[0002] The nitrogen cycle is a fundamental biogeochemical process that sustains life on Earth, and nitrate is an important intermediate in the nitrogen cycle. The concentration of nitrate in nature is usually at a relatively low level, while human activities, especially agricultural activities and industrial emissions, have greatly increased the emissions of nitrate. Approximately 26.22 million tons of nitrate are discharged into water bodies in various ways globally every year, leading to a sharp increase in the nitrate concentration in water bodies, which in turn triggers a series of environmental and health problems.

[0003] Commonly used nitrate reduction catalysts mainly include noble metals (such as palladium and platinum) and transition metal oxides, which have been widely studied due to their excellent catalytic performance. However, due to their high cost, their popularization in large-scale applications is limited. Summary of the Invention

[0004] Aiming at the above technical problems existing in the prior art, the purpose of the present invention is to provide a Pt CSA / Cu 2 O / NF composite material and its application in electrocatalytic reduction of nitrate to ammonia.

[0005] The technical solution adopted by the present invention is as follows:

[0006] A Pt CSA / Cu 2 O / NF composite material is prepared by the following steps:

[0007] 1) Preparation of CuO / NF: After the nickel foam NF is cleaned and pretreated, the pretreated nickel foam NF is used as the cathode, the electrolyte solution is an aqueous solution of Cu(NO 3 ) 2 , and a platinum sheet is used as the anode counter electrode to carry out electrochemical deposition at a preset constant voltage, so that Cu(OH) 2 is deposited on the nickel foam NF to obtain a Cu(OH) 2 / NF electrode sheet. The Cu(OH) 2 / NF electrode sheet is calcined at high temperature in a nitrogen atmosphere to obtain a CuO / NF electrode sheet;

[0008] 2) Electroreduction treatment: Using the CuO / NF electrode sheet obtained in step 1) as the cathode, the electrolyte solution is an electrolyte solution, and a platinum sheet is used as the anode counter electrode to carry out electroreduction at a preset constant voltage, so that CuO on the cathode is transformed into Cu 2 O to obtain Cu2 O / NF electrode sheet;

[0009] 3) Pt on Cu 2 Loading of Pt on O / NF: Dissolve the platinum source in the electrolyte solution. Using the Cu 2 O / NF electrode sheet obtained in step 2) as the cathode and a platinum sheet as the anode counter electrode, perform electrodeposition at a preset constant voltage to reduce the platinum source to a coexisting form of Pt single atoms and clusters, denoted as Pt CSA , Pt CSA is loaded on the Cu 2 O / NF electrode sheet, and after natural drying, obtain Pt CSA / Cu 2 O / NF composite material.

[0010] Further, the concentration of the Cu(NO 3 ) 2 aqueous solution in step 1) is 0.04 - 0.06 M, the constant voltage is 0.2 - 0.4 V, and the time for electrochemical deposition is 0.5 - 2 h.

[0011] Further, the electrolyte in step 2) is an aqueous solution of sodium sulfate with a concentration of 0.05 - 0.2 M, the voltage for electroreduction is -0.2 V to -0.4 V, and the electroreduction time is 15 - 30 minutes.

[0012] Further, the specific process of step 3) is: Using the CuO / NF electrode sheet as the working electrode, a platinum sheet as the counter electrode, the electrolyte is an aqueous solution of sodium sulfate with a concentration of 0.05 - 0.2 M, the platinum source is chloroplatinic acid hexahydrate, and the amount of Pt in the platinum source is 0.19 - 0.4 mg / cm based on the electrode area of the nickel foam NF substrate 2 ; the constant voltage for the electrodeposition is -0.1 V to -0.3 V, and the electrodeposition time is 10 - 30 minutes.

[0013] Further, the temperature for high-temperature calcination in step 1) is 500 - 600 °C, and the calcination time is 1 - 3 h.

[0014] The present invention also provides the application of the described Pt CSA / Cu 2 O / NF composite material in the electrocatalytic reduction of nitrate to ammonia. The application method is: The electrocatalytic reduction device for electrocatalytically reducing nitrate to ammonia uses an H-type two-compartment electrolytic cell, separated by a cation exchange membrane between the cathode compartment and the anode compartment. Using the Pt CSA / Cu 2 O / NF composite material as the cathode working electrode, a platinum electrode as the anode counter electrode, supplemented with an Ag / AgCl electrode as the reference electrode. Add electrolytes to both the cathode compartment and the anode compartment, and the electrolyte in the cathode compartment contains nitrate, and perform electrocatalytic reduction of nitrate to ammonia at a constant voltage.

[0015] Further, during the reaction of electrocatalytically reducing nitrate to ammonia, the potential of the constant voltage is -0.3V to -0.4V, preferably -0.35V to -0.39V.

[0016] Further, the electrolyte is an aqueous solution of sodium sulfate with a concentration of 0.05 - 0.3M.

[0017] Compared with the prior art, the beneficial effects achieved by the present invention are as follows:

[0018] 1) The present invention utilizes the Pt CSA / Cu 2 O / NF composite electrode. Through the electrochemically reduction method, it can achieve the conversion of refractory nitrate pollutants in water to ammonia at a low potential (-0.39V vs. RHE), thereby effectively removing nitrate pollutants in water. The operation is simple and the management is convenient, having extensive social and economic benefits.

[0019] 2) The present invention precisely regulates the atomic dispersion degree of platinum through the in-situ electrochemical deposition method, constructs a single-atom - nanocluster gradient distribution structure (Pt CSA / Cu 2 O / NF), realizes an ultra-low loading amount of noble metal platinum (only 1 / 75 of the traditional platinum-based catalyst), greatly improves its atomic utilization rate, and significantly alleviates the industrialization bottleneck problem of the high cost of noble metal catalysts.

[0020] 3) The Pt CSA / Cu 2 O / NF composite electrode applied in the present invention is synthesized by a green and environmentally friendly method, and has characteristics such as a large number of catalytic active sites and a long service life. It has ultra-high catalytic removal and degradation performance for nitrate pollutants and has the characteristic of a long catalytic life, having a very broad application prospect in the application of electrocatalytic treatment of nitrate in wastewater. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 is a schematic structural diagram of the device for electrocatalytically reducing nitrate to ammonia used in the present invention;

[0022] Figure 2 is a scanning electron microscope image of the Pt CSA / Cu 2 O / NF composite material prepared in Example 1;

[0023] Figure 3 is a graph showing the change of the concentration of each substance in the cathode solution with time during the electrocatalytic reaction of reducing nitrate by the Pt CSA / Cu 2 O / NF prepared in Example 1 within 4h;

[0024] Figure 4 It is a comparison diagram of the effect of reducing nitrate to ammonia in Examples 1-5;

[0025] Figure 5 It is a comparison diagram of the effect of the electrocatalytic reaction of reducing nitrate to ammonia when the cathode uses the composite materials of Examples 1, 8-9 and the nickel foam substrate respectively; Figure 5 In the bar chart, the results are selectivity, and in the dotted line chart, the results are conversion rate.

[0026] Figure 6 It is the result diagram of the electrocatalytic reduction reaction using the Pt CSA / Cu 2 O / NF composite material in Example 10 for 10 repetitions. Specific embodiments

[0027] The present invention will be further described below in conjunction with specific embodiments, but the protection scope of the present invention is not limited thereto.

[0028] The structural schematic diagram of the electrocatalytic reduction of nitrate to ammonia device used in the following Examples 1-7 is as Figure 1 shown.

[0029] As Figure 1 shown, the electrocatalytic reduction of nitrate to ammonia device includes an electrolytic cell and an electrochemical workstation. The electrolytic cell includes an anode cell for storing the anode solution and the counter electrode, and a cathode cell for storing the cathode solution, the working electrode and the reference electrode (the cathode cell is connected to the reference cell), and a cation exchange membrane.

[0030] A sampling port is arranged at the upper part of the cathode cell; a communication pipeline is arranged at the bottom of the anode cell and the cathode cell; a cation exchange membrane for separating the anode cell and the cathode cell is arranged in the communication pipeline. Among them, the counter electrode is a platinum electrode; the reference electrode is an Ag / AgCl electrode; the working electrode is the Pt CSA / Cu 2 O / NF composite material provided in Example 1; the anode solution is an aqueous solution of sodium sulfate (the concentration of sodium sulfate is 0.1 mol / L); the cathode solution is a mixed aqueous solution of sodium sulfate and sodium nitrate (the concentration of sodium sulfate is 0.1 mol / L, and the content of sodium nitrate is 50 mg / L). The counter electrode, the working electrode and the reference electrode are all connected to the electrochemical workstation.

[0031] The electrode areas of the counter electrode and the working electrode are both 4 cm 2 (2 cm × 2 cm); with an Ag / AgCl electrode as the reference electrode, the electrode spacing is 8 cm. The reaction volume of the electrolyte in the cathode cell is 150 ml. The reaction volume of the electrolyte in the anode cell is 150 ml.

[0032] Example 1

[0033] A method using Pt CSA / Cu 2 O / NF composite material for electrocatalytic reduction of nitrate to ammonia; it utilizes the electrocatalytic reduction of nitrate reaction to achieve the degradation of nitrate; the Pt CSA / Cu 2 The preparation method of O / NF composite material includes the following steps:

[0034] 1) Preparation of Cu(OH) 2 / NF electrode sheet: First, cut the foam nickel and place it in a 3mol / L hydrochloric acid solution for ultrasonic cleaning for half an hour. After cleaning, wash it with deionized water until neutral, then wash it with ethanol three times and dry it. Then, use the foam nickel as the cathode, the platinum sheet as the anode, and the silver / silver chloride (Ag / AgCl) electrode as the reference electrode. Weigh 0.475g of copper nitrate trihydrate solid and dissolve it in deionized water to prepare a 0.05mol / L copper nitrate electrolyte. Perform electrodeposition at a constant voltage of 0.31V vs. RHE for 1 hour to obtain the Cu(OH) 2 / NF electrode sheet.

[0035] 2) Preparation of Cu 2 O / NF electrode sheet: Calcinate the Cu(OH) 2 / NF electrode sheet in a nitrogen atmosphere at 550°C for 2h to obtain the CuO / NF electrode sheet. Then, use the CuO / NF electrode sheet as the cathode, the platinum sheet as the anode, and the silver / silver chloride (Ag / AgCl) electrode as the reference electrode, and perform electroreduction at a constant voltage of -0.39V vs. RHE in a 0.1mol / L sodium sulfate solution for 15 minutes to obtain the Cu 2 O / NF electrode sheet.

[0036] 3) Preparation of Pt CSA / Cu 2 O / NF composite material: Dissolve 4.1mg of chloroplatinic acid hexahydrate in 50mL of 0.1mol / L Na 2 SO 4 solution at room temperature to obtain the solution as the electrolyte. Then, use the Cu 2 O / NF electrode sheet as the cathode, the platinum sheet as the anode, and the silver / silver chloride (Ag / AgCl) electrode as the reference electrode, and perform electrodeposition in the prepared electrolyte at a constant voltage method for 15 minutes, with a voltage of -0.19V vs. RHE, and finally obtain the Pt CSA / Cu 2 O / NF composite material.

[0037] The Pt of Example 1 CSA / Cu 2Method for electrocatalytic reduction of nitrate to ammonia using O / NF composite material, the specific process is as follows:

[0038] Construct an electrocatalytic reduction device for nitrate to ammonia with an H-type two-compartment structure as shown in Figure 1 Use the Pt CSA / Cu 2 O / NF electrode sheet composite material prepared in Example 1 as the cathode working electrode, a platinum electrode as the anode counter electrode. The electrode areas of the working electrode and the counter electrode are both 4 cm 2 (2 cm × 2 cm), supplemented with an Ag / AgCl electrode as the reference electrode. The electrode distance between the cathode and the anode is 8 cm. The constant voltage is -0.39 V vs. RHE. The electrolyte in the cathode cell is a mixed aqueous solution of sodium sulfate and sodium nitrate (the concentration of sodium sulfate is 0.1 mol / L), and the content of sodium nitrate is 50 mg / L). The counter electrode, working electrode, and reference electrode are all connected to an electrochemical workstation.

[0039] Simulate natural inorganic wastewater. The reaction volume of the electrolyte in the cathode cell is 150 ml. The electrolyte in the anode cell is an aqueous solution of sodium sulfate with a concentration of 0.1 mol / L, and the reaction volume of the electrolyte in the anode cell is 150 ml. And samples of the electrolyte in the cathode cell are taken and analyzed at different times to conduct the electrocatalytic reaction. The electrocatalytic reaction results for each time period are shown in Table 1, and the results of the electrocatalytic reaction for 4 h are as shown in Figure 4 and Table 2.

[0040] In the electrocatalytic reaction of nitrate reduction by Pt CSA / Cu 2 O / NF prepared in Example 1 within 4 h, the changes in the concentrations of various substances in the cathode solution with time are shown in Figure 3 . From Figure 3 it can be seen that at 120 min of the electrocatalytic reaction, nitrate is completely converted, and the selectivity of ammonium ions is close to 100%.

[0041] Examples 2 - 5:

[0042] Repeat the experimental steps of Example 1 for Examples 2 - 5. The difference is only that "in the experiment of electrocatalytic reduction of nitrate to ammonia using Pt CSA / Cu 2 O / NF composite material, the constant voltage of the electrocatalytic reaction is replaced from -0.39 V vs. RHE to -0.19 V vs. RHE, -0.29 V vs. RHE, -0.49 V vs. RHE, and -0.59 V vs. RHE", and the other conditions remain unchanged. The experimental results are: the electrocatalytic reaction results for each time period are shown in Table 1, and the results of the electrocatalytic reaction for 4 h are as shown in Figure 4 and Table 2.

[0043] Table 1. Pt CSA / Cu 2 Conversion rate of electrocatalytic reduction of nitrate to ammonia by Pt

[0044]

[0045] Table 2. Pt CSA / Cu 2 Selectivity of ammonium after 4 h of electrocatalytic reduction of nitrate to ammonia by Pt

[0046]

[0047] From Table 1, Table 2 and Figure 3 it can be seen that using Pt CSA / Cu 2 O / NF composite material can exhibit excellent nitrate reduction performance at a low working potential of -0.39 V vs. RHE, remove all 50 mg / L nitrate pollutants in wastewater within a short time of 1.5 h, and the selectivity of ammonium is close to 100%.

[0048] Example 6

[0049] Preparation method of Pt SA / Cu 2 O / NF composite material repeats Example 1, the difference is only that in step 3), when electrodepositing Pt, the dosage of chloroplatinic acid hexahydrate is replaced from 4.1 mg to 2.05 mg to control the formation of Pt single atoms, and the other conditions remain unchanged. Finally, Pt SA / Cu 2 O / NF composite material is obtained.

[0050] Application of Pt SA / Cu 2 O / NF composite material in the electrocatalytic reduction of nitrate to ammonia reaction, the specific experimental conditions repeat Example 1, and the results of the electrocatalytic reaction at each time period are shown in Table 3, and the results of the electrocatalytic reaction for 4 h are shown in Table 4.

[0051] Example 7

[0052] Preparation method of Pt C / Cu 2 O / NF composite material repeats Example 1, the difference is only that in step 3), when electrodepositing Pt, the dosage of chloroplatinic acid hexahydrate is replaced from 4.1 mg to 16.4 mg to control the formation of Pt clusters, and the other conditions remain unchanged. Finally, Pt C / Cu 2 O / NF composite material is obtained.

[0053] Example 7 Pt C / Cu 2 The O / NF composite material is applied to the reaction of electrocatalytic reduction of nitrate to ammonia. The specific experimental conditions are repeated in Example 1. The results of the electrocatalytic reaction at each time period are shown in Table 3, and the results of the electrocatalytic reaction for 4 h are shown in Table 4.

[0054] Example 8

[0055] Example 8 Cu 2 The preparation method of the O / NF composite material is repeated in Example 1, and the difference is only that the step of electrodepositing Pt in step 3) is omitted, that is, Pt is not loaded, and the other conditions remain unchanged. Finally, the Cu 2 O / NF composite material is obtained.

[0056] Example 8 Cu 2 The O / NF composite material is applied to the reaction of electrocatalytic reduction of nitrate to ammonia. The specific experimental conditions are repeated in Example 1. The results of the electrocatalytic reaction at each time period are shown in Table 3, and the results of the electrocatalytic reaction for 4 h are as Figure 5 shown in Table 4.

[0057] Example 9

[0058] Example 9 Pt CSA The preparation method of the / NF composite material includes the following steps:

[0059] 1) First, the cut nickel foam is placed in a 3 mol / L hydrochloric acid solution and ultrasonically cleaned for half an hour. After cleaning, it is washed with deionized water until neutral, and then washed with ethanol three times and dried.

[0060] 2) At room temperature, 4.1 mg of chloroplatinic acid hexahydrate is dissolved in 50 mL of 0.1 mol / L Na 2 SO 4 solution to obtain the solution as the electrolyte. Then, using nickel foam as the cathode, a platinum sheet as the anode, and a silver / silver chloride (Ag / AgCl) electrode as the reference electrode, electro-deposition is carried out in the prepared electrolyte by the constant voltage method for 15 minutes, with a voltage of -0.39 V vs. RHE, and finally the Pt CSA / NF composite material is obtained.

[0061] Example 9 Pt CSA The / NF composite material is applied to the reaction of electrocatalytic reduction of nitrate to ammonia. The specific experimental conditions are repeated in Example 1. The results of the electrocatalytic reaction at each time period are shown in Table 3, and the results of the electrocatalytic reaction for 4 h are as Figure 5 shown in Table 4.

[0062] Table 3. Pt CSA / Cu 2Conversion rate of electrocatalytic reduction of nitrate to ammonia by O / NF composite electrode and control sample for 4 h

[0063]

[0064] Table 4. Pt CSA / Cu 2 Selectivity of ammonium by O / NF composite electrode and control sample for electrocatalytic reduction of nitrate to ammonia for 4 h

[0065]

[0066] As can be seen from Table 3, Table 4 and Figure 5 it can be seen that by adding a low loading of Pt, Pt CSA / Cu 2 O / NF composite material can completely convert nitrate to ammonia and remove all 50 mg / L nitrate pollutants in the wastewater. Controlling the Pt loading to form Pt single atoms and clusters coexisting in Pt CSA / Cu 2 O / NF composite material shows superior nitrate reduction performance compared with Pt C / Cu 2 O / NF and Pt SA / Cu 2 O / NF exhibits excellent nitrate reduction performance, indicating that the single-atom-cluster coexisting Pt CSA / Cu 2 O / NF composite material constructed by precisely regulating the Pt loading (0.02 wt%) shows significant advantages in the electrocatalytic reduction reaction of nitrate.

[0067] Example 10

[0068] After the electrocatalytic reduction reaction of nitrate in Example 1 was carried out for 4 h, the electrolysis was stopped. The cathode solution was emptied and fresh cathode solution was replaced for the next electrocatalytic reaction; this was repeated 10 times to verify the recycling performance of the Pt CSA / Cu 2 O / NF composite material. The results of electrocatalytic reduction and dechlorination of the Pt CSA / Cu 2 O / NF composite material after being reused 10 times are as shown in Figure 6 shown.

[0069] From Figure 6 it can be seen that during the 10 - time reuse of the Pt CSA / Cu 2 O / NF composite material, its electrocatalytic performance stability is good.

[0070] The content described in this specification is only an enumeration of the implementation forms of the inventive concept, and the protection scope of the present invention should not be regarded as limited to the specific forms stated in the embodiments.

Claims

1. A Pt CSA / Cu2O / NF composite material, characterized in that The preparation was carried out by the following steps: 1) Preparation of CuO / NF: After the nickel foam NF is cleaned and pretreated, the pretreated nickel foam NF is used as a cathode, a Cu(NO3)2 aqueous solution is used as an electrolyte, and a platinum sheet is used as an anode to perform electrochemical deposition on the electrode at a preset constant voltage, so that Cu(OH)2 is deposited on the nickel foam NF to obtain a Cu(OH)2 / NF electrode sheet, and the Cu(OH)2 / NF electrode sheet is calcined at a high temperature in a nitrogen atmosphere to obtain a CuO / NF electrode sheet; 2) Electro-reduction treatment: The CuO / NF electrode sheet in step 1) is used as the cathode, the electrolyte solution is used as the electrolyte, and the platinum sheet is used as the anode to perform electro-reduction at a preset constant voltage to convert the CuO on the cathode into Cu2O to obtain a Cu2O / NF electrode sheet; 3) Loading of Pt on Cu2O / NF: The platinum source is dissolved in the electrolyte solution, and the Cu2O / NF electrode sheet obtained in step 2) is used as the cathode and the platinum sheet is used as the anode counter electrode. Electrodeposition is performed at a preset constant voltage to reduce the platinum source to the coexistence of Pt single atoms and clusters, which is recorded as Pt CSA , Pt CSA Pt was loaded on the Cu2O / NF electrode sheet and obtained after natural drying. CSA / Cu2O / NF composites.

2. A Pt as claimed in claim 1 CSA / Cu2O / NF composite material, characterized in that The concentration of the Cu(NO3)2 aqueous solution in step 1) is 0.04-0.06M, the constant voltage is 0.2-0.4V, and the electrochemical deposition time is 0.5-2h.

3. A Pt as claimed in claim 1 CSA / Cu2O / NF composite material, characterized in that In step 2), the electrolyte is a 0.05-0.2M sodium sulfate aqueous solution, the electroreduction voltage is -0.2V to -0.4V, and the electroreduction time is 15-30 minutes.

4. A Pt as claimed in claim 1 CSA / Cu2O / NF composite material, characterized in that The specific process of step 3) is: the CuO / NF electrode sheet is used as the working electrode, the platinum sheet is used as the counter electrode, the electrolyte is a 0.05-0.2M sodium sulfate aqueous solution, the platinum source is hexahydrated chloroplatinic acid, and the amount of Pt in the platinum source is 0.19-0.4 mg / cm based on the electrode area of ​​the nickel foam NF substrate. 2 ; The constant voltage of the electrodeposition is -0.1V to -0.3V, and the electrodeposition time is 10-30 minutes.

5. A Pt as claimed in claim 1 CSA / Cu2O / NF composite material, characterized in that The temperature of high temperature calcination in step 1) is 500-600° C. and the calcination time is 1-3 hours.

6. A Pt as claimed in claim 1 CSA Application of / Cu2O / NF composite materials in electrocatalytic reduction of nitrate to ammonia.

7. The use according to claim 6, characterized in that The electrocatalytic reduction device for electrocatalytic reduction of nitrate to ammonia adopts an H-type two-chamber electrolytic cell, wherein the cathode chamber and the anode chamber are separated by a cation exchange membrane. CSA The Ag / AgCl electrode is used as the reference electrode, and the Ag / Cu2O / NF composite material is used as the cathode working electrode. The Ag / AgCl electrode is used as the anode counter electrode. Electrolyte is added to both the cathode chamber and the anode chamber. The electrolyte in the cathode chamber contains nitrate, and electrocatalytic reduction of nitrate is carried out to produce ammonia under constant voltage.

8. The use according to claim 7, characterized in that During the electrocatalytic reduction of nitrate to ammonia, the constant voltage potential is -0.3V to -0.4V, preferably -0.35V to -0.39V.

9. The use according to claim 7, characterized in that The electrolyte is a sodium sulfate aqueous solution with a concentration of 0.05-0.3M.

Citation Information

Patent Citations

  • Preparation method and application for platinum / cuprous oxide film compound

    CN111185193A

  • Cascade electrocatalyst Cu / Cu2O / CuAl-LDH for nitrate reduction synthesis of ammonia as well as preparation method and application of cascade electrocatalyst Cu / Cu2O / CuAl-LDH

    CN118516701A

  • Preparation method and application of three-dimensional structured electric cathode based on cuprous oxide

    US20240410066A1

  • Atomic hydrogen provision by cobalt sites in catalyst configurations for ammonia production

    US20250066928A1